Regulation of Vesicular Traffic at the T Cell Immune Synapse: Lessons from the Primary Cilium. (23rd January 2015) - Finetti, Francesca; Onnis, Anna; Baldari, Cosima T.
Abstract The signals that orchestrate the process of T cell activation are coordinated at the specialized interface that forms upon contact with an antigen presenting cell displaying a specific MHC‐associated peptide ligand, known as the immune synapse. The central role of vesicular traffic in the assembly of the immune synapse has emerged only in recent years with the finding that sustained T‐cell receptor (TCR) signaling involves delivery of TCR/CD3 complexes from an intracellular pool associated with recycling endosomes. A number of receptors as well as membrane‐associated signaling mediators have since been demonstrated to exploit this process to localize to the immune synapse. Here, we will review our current understanding of the mechanisms responsible for TCR recycling, with a focus on the intraflagellar transport system, a multimolecular complex that is responsible for the assembly and function of the primary cilium which we have recently implicated in polarized endosome recycling to the immune synapse. <inline-graphic xlink:href="ark:/27927/pgj4db29x" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />